Sustainability in Drug and Nanoparticle Processing - Fischer, Dagmar (Springer Science and Business Media Deutschland GmbH, 2024)
The formulation of drugs in poly(lactic-co-glycolic acid) (PLGA) nanoparticles can be accomplished by various methods, with nanoprecipitation and nanoemulsion being among the most commonly used manufacturing techniques to provide access to high-quality nanomaterials with reproducible quality. Current trends turned to sustainability and green concepts leading to a re-thinking of these techniques, particularly as the conventional solvents for the dissolution of the polymer suffer from limitations like hazards for human health and natural environment. This chapter gives an overview about the different excipients used in classical nanoformulations with a special focus on the currently applied organic solvents. As alternatives, the status quo of green, sustainable, and alternative solvents regarding their application, advantages, and limitations will be highlighted as well as the role of physicochemical solvent characteristics like water miscibility, viscosity, and vapor pressure for the selection of the formulation process, and for particle characteristics. New alternative solvents will be introduced for PLGA nanoparticle formation and compared regarding particle characteristics and biological effects as well as for in situ particle formation in a matrix consisting of nanocellulose. Conclusively, new alternative solvents are available that present a significant advancement toward the replacement of organic solvents in PLGA nanoparticle formulations.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Drug delivery; Nanoparticles; PLGA; Polymer; Sustainability